Case Report: Rosai-Dorfman Disease Involving Sellar Region in a Pediatric Patient: A Case Report and Systematic Review of Literature - Zhang, Yi; Liu, Jie; Zhu, Jianyu; Zhou, Xiang; Zhang, Kun; Wang, Shirui; Ma, Wenbin; Pan, Hui; Wang, Renzhi; Zhu, Huijuan; Yao, Yong (Frontiers in Medicine, 2020)
Rosai-Dorfman disease (RDD) is an extremely rare histiocytic disorder characterized by cervical lymphadenopathy, while the involvement of sellar region is less observed. Here we report a pediatric patient who was initially suspected as sellar germinoma but later identified as RDD. We also conducted a systematic review about RDD involving sellar region. A total of only 12 cases were included and analyzed in our study in terms of clinical presentation, endocrine abnormality, radiological features, pathology, treatment and follow up. The most common neurological manifestations of sellar RDD is diabetes insipidus and visual changes. Two typical kinds of MRI manifestations were presented in sellar RDD; one is like meningioma-like mass lesions, another showing infiltrative pattern that demonstrates hyperintense areas on T2WI. Currently, the treatment of RDD is tailored to the individual clinical circumstances. For sellar RDD, surgical treatment can be considered to completely remove or debulk the tumor.